A Systematic Review to Guide Future Efforts in the Determination of Genetic Causes of Pregnancy Loss - Carey, Andrew Z.; Blue, Nathan R.; Varner, Michael W.; Page, Jessica M.; Chaiyakunapruk, Nathorn; Quinlan, Aaron R.; Branch, D. Ware; Silver, Robert M.; Workalemahu, Tsegaselassie (Frontiers in Reproductive Health, 2021)
Background: Pregnancy loss is the most common obstetric complication occurring in almost 30% of conceptions overall and in 12-14% of clinically recognized pregnancies. Pregnancy loss has strong genetic underpinnings, and despite this consensus, our understanding of its genetic causes remains limited. We conducted a systematic review of genetic factors in pregnancy loss to identify strategies to guide future research. Methods: To synthesize data from population-based association studies on genetics of pregnancy loss, we searched PubMed for relevant articles published between 01/01/2000-01/01/2020. We excluded review articles, case studies, studies with limited sample sizes to detect associations (N<4), descriptive studies, commentaries, and studies with non-genetic etiologies. Studies were classified based on developmental periods in gestation to synthesize data across various developmental epochs. Results: Our search yielded 580 potential titles with 107 (18%) eligible after title/abstract review. Of these, 54 (50%) were selected for systematic review after full-text review. These studies examined either early pregnancy (n=9 [17%]), stillbirth (n=10 [18%]), recurrent pregnancy loss (n=32 [59%]), unclassified pregnancy loss (n=3 [4%]) as their primary outcomes. Multiple genetic pathways that are essential for embryonic/fetal survival as well as human development were identified. Conclusion: Several genetic pathways may play a role in pregnancy loss across developmental periods in gestation. Systematic evaluation of pregnancy loss across developmental epochs, utilizing whole genome sequencing in families may further elucidate causal genetic mechanisms and identify other pathways critical for embryonic/fetal survival.